Pengaruh Konflik dan Budaya Organisasi Terhadap Kinerja Pada Badan Pendapatan Daerah Provinsi Sumatera Selatan - Antika, Tri; Sinarti, Tri (Jurnal Ilmiah Bina Manajemen, 2019)
Performance, knowing the Effect of Organizational Culture on Performance and knowing the effect of Conflict and Organizational Culture on Performance in the Regional Revenue Agency of the Province of South Sumatra.This study uses a questionnaire as a data collection technique with the number of samples used by 51 employees. This study uses the help of SPSS Version 22 software to analyze data The results of the t-test analysis show that the value of the Conflict variable (X1) is 3,619, and the organizational culture is 4,185 so the value of tcount> t table is 3,619> 1,676 with a significance level of 0.001 <0.05 for Conflict (X1) and 4,185> 1,676 for Culture Organization (X2) with a significance level of 0,000 <0,05, then Ho is rejected and Ha is accepted which means that the conflict partially has a significant effect on employee performance and Organizational Culture partially has a significant effect on employee performance. Based on the results of the F test obtained Fcount value of 17.180 with a Ftable value of 3.16, the value of Fcount> Ftable is 17.180> 3.19. Significance value = 0.000áµ‡ <Î± = 0.05 then Ho is rejected and Ha is accepted, meaning that there is a significant influence between Conflict and Organizational Culture on Employee Performance. Furthermore, the R square value obtained is 0.417, which means that employee performance at the Regional Revenue Agency can be explained by Conflict and Organizational Culture of 41.7%, while the remaining 58.3% is explained by other variables not included in this study, such as motivation, environment work and training. This shows that the free variables (Conflict and Organizational Culture) only provide part of the information needed to predict the dependent variable (Performance).